TO THE HISTORY OF COVERING THE PECULIARITIES OF THE DAGESTAN CARPET WEAVING - Ramazanova, Z B; Garunova, S M (History, Archeology and Ethnography of the Caucasus, 2017)
he Article provides an overview of the historiography of the description of Dagestan carpet-weaving as a component of the domestic economy, material culture and aesthetic consciousness, as well as some ornamental and compositional and technical characteristics of local varieties of carpets and rugs. Analysis of literature data and field ethnographic materials suggests that Dagestan carpet-weaving is characterized by ornamental features and compositional diversity; by abundance of local centers which used to produce these carpets and rugs; by art and technical features of Dagestan carpets which visibly testified in which part of Dagestan, in what village they are woven. Actually, this seems the most impressive feature of the Dagestan carpet culture. It is noteworthy that many well known types of Caucasian rugs are named as Lezgi (Mirakh, Akhty, Kabir, Akhty, Zahur (Zeihur), Chi-Chi), Kumyk (Kayakent, Kumtorkala), Avar (Tlyarota) villages. In the World there are no analogues to ornamental and color composition of flat-weave carpet types "dum","davagin", "salmag" "soumakh ", which were woven in a certain Kumyk, Avar, Lezgi villages. So, the particularly of Dagestan carpet-weaving is expressed by: a) the abundance of original carpet designs, developed to canonical level of perfection and clearly localized in the districts and villages; b) variability of the ornamental and technological characteristics: с) plurality of local types of carpets; g) fineness of weaving technique; d) quality of wool of the Dagestan mountain breed of sheep; e) coloring properties of the Derbent madder roots which, comparing with all known World species of this plant, has a superior content of the red colorant. All this, combined with the skillful, painstaking work of the weavers, determines the finesse of the Dagestan carpets, which is easily detected by the naked eye and without special knowledge.